L-Lactate Regulates the Expression of Synaptic Plasticity and Neuroprotection Genes in Cortical Neurons: A Transcriptome Analysis - Margineanu, Michael B.; Mahmood, Hanan; Fiumelli, Hubert; Magistretti, Pierre J. (Frontiers in Molecular Neuroscience, 2018)
Lactate, a product of aerobic glycolysis in astrocytes, is required for memory formation and consolidation, and has recently emerged as a signaling molecule for neurons and various cell types in peripheral tissues. In particular lactate stimulates mRNA expression of a few plasticity-related genes. Here, we describe a RNA-Seq study that unravels genome-wide transcriptomic responses to this energy metabolite in cortical neurons. Our results show that mRNA expression of 20 immediate-early genes involved in the MAPK signaling pathway and in synaptic plasticity were increased by more than 2-fold following 1h of lactate stimulation. This effect was dependent on NMDA receptor activity since it was prevented by pre-treatment with MK-801. Comparison with published datasets showed that a significant proportion of genes modulated by lactate were similarly regulated by a stimulation protocol activating specifically synaptic NMDA receptors known to result in upregulation of pro-survival and downregulation of pro-death genes. Remarkably, transcriptional responses to lactate were reproduced by NADH (for 74 of the 113 genes, FDR<0.05), suggesting a redox-dependent mechanism of action. Longer-term gene expression changes observed after 6h of lactate treatment affected genes involved in regulating neuronal excitability and genes coding for proteins localized at synapses. Gene set enrichment analyses performed with ranked lists of expressed genes revealed effects on molecular functions involved in epigenetic modulation, and on processes relevant to sleep physiology and behavioral phenotypes such as anxiety and hyperactivity. Overall, these results strengthen the notion that lactate effectively regulates activity-dependent and synaptic genes, and highlight new signaling effects of lactate in plasticity and neuroprotection.